Osutost dreves na ploskvah intenzivnega monitoringa gozdnih ekosistemov v Sloveniji v zadnjih dveh desetletjih - Pintar, Anže Martin (Gozdarski vestnik, 2024)
Before introducing more accurate physical-chemical measurements (analytical measurements of the content of certain elements in the precipitation and foliar samples) to evaluate forest damage or response of the forests to pollution, indirect forms of pollution impact the monitoring of the forest ecosystems or assessment of pollutant impacts on the trees were mostly enforced in the framework of the ICP forests. One of the important indicators is the crown defoliation assessment. It represents a visually assessed proportion of the missing assimilation organs (leaves or needles) compared to a normally vital tree of equal social status, same tree species, and equal site. The assessment has an accuracy of 5 %. A tree is considered damaged if more than 25 % of the tree crown is defoliated (at least a quarter of its foliage is missing). The article presents the results of the defoliation status monitoring on ten intensive monitoring plots (ICP Forests) after 2003. In recent years, the plots most affected by crown defoliation were Fondek (European beech), Gropajski bori (Austrian pine), Gorica (European beech), and Lontovž (European beech). Defoliation has been increasing on all four plots except Gorica over the last few years. The Gropajski bori plot is experiencing a transition period; artificially planted Austrian pine is slowly being replaced by autochthonous broadleaves. Recently, the most defoliated trees have been European hophornbeam and Austrian pine on the Gropajski bori plot, pedunculate oak on the Krakovski gozd and Murska šuma plots, and European beech on the Fondek plot. Since 2014, the average defoliation has gradually worsened on over half of the plots, especially those where regeneration phase is replacing the old stand. In 2022, summer drought with its associated factors is hypothesised to have been the main contributor to the increased defoliation rate.
Keywords: ICP Forests; iglavci; intenzivni monitoring; listavci; osutost dreves; stanje gozdov